MiR-3194-3p Inhibits Breast Cancer Progression by Targeting Aquaporin1 - Wei, Min; Yu, Hailang; Cai, Cuixia; Gao, Rui; Liu, Xuhua; Zhu, Huimin (Frontiers in Oncology, 2020)
Increasing evidences indicate that the abnormal expression of Aquaporin1 (AQP1) is associated with a wide variety of human cancers including breast cancer (BC). In the present study, we found miR-3194-3p regulated AQP1 expression targeting the 3'-untranslated region (UTR) using miRNA target prediction algorithms. miR-3194-3p expression was markedly down-regulated and AQP1 expression was significantly up-regulated in BC tissues and cell lines as compared with adjacent nontumor tissues and a normal human mammary epithelial cell line. A statistically significant inverse correlation was found between AQP1 and miR-3194-3p levels in tumor tissues from 30 BC patients. Gain- and loss-of-function assays demonstrated that miR-3194-3p mimic remarkably inhibited cell proliferation, migration, invasion and promoted apoptosis in MDA-MB-231 cells, while miR-3194-3p inhibitors notably promoted cell proliferation, migration, invasion and inhibited apoptosis in MCF-7 cells. Dual-luciferase reporter assay confirmed that AQP1 was a direct target gene of miR-3194-3p. Over-expression of AQP1 by pBABE-puro-AQP1 vector partially abrogated the effect of miR-3194-3p mimic in MDA-MB-231 cells. Taken together, these results suggest that miR-3194-3p suppresses BC cell proliferation, migration and invasion by targeting AQP1, providing a novel insight into the BC treatment.